Pengaruh Pengetahuan Keuangan, Sikap Keuangan Dan Etika Islam Dalam Manajemen Keuangan Pada Perilaku Manajemen Keuangan. (Studi Pada Perilaku UMKM Rumah Pengusaha Malang Raya (RPMR) - Siti Suhaebah; Ronny Malavia Mardani; Eris Dianawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The purpose of this research is to find out and analyze how the influence of Financial Knowledge, Financial Attitudes and Islamic Ethics in Financial Management on Financial Management Behavior. The population used in this study is the Entrepreneur of RPMR Malang Raya. The technique used in sampling in this study is purposive sampling. The variables in this study are Financial Knowledge, Financial Attitude, Islamic Ethics in Financial Management and Financial Management Behavior. The data collection method used in this study was a questionnaire given to customers and the library, namely from journals and articles. The analysis used is multiple linear regression.The results of this study explain that the financial knowledge variable has an effect on Financial Management Behavior, the Financial Attitude variable has an effect on Financial Management Behavior, the Islamic Ethics variable in Financial Management has an effect on Financial Management Behavior. Keywords : Good Corporate Governance, Board of Directors, Independent Board of Commissioners, Managerial Ownership, Institutional Ownership, Liquidity Ratio, Leverage Ratio, Profitability Ratio and Financial Distress